Representative Bias Effects on Investment Performance During Stock Market Volatility Events - Dedi Hariyanto (IECON: International Economics and Business Conference, 2025)
This study investigates the influence of familiarity bias and attention grabbing on abnormal returns during black swan events. The analysis employs the traditional Capital Asset Pricing Model, expanded with prospect theory and the Fama and French Three- Factor Model, incorporating psychological variables such as familiarity and attention grabbing. The population comprises all companies listed and actively traded on the Indonesia Stock Exchange from 1997 to 2020. A systematic sampling method was used to determine the sample, resulting in 5,615 observations based on trading days over 23 years across nine sectors. The findings reveal that familiarity bias does not uniformly occur across all sectors during black swan events. Sectors significantly affected, either positively or negatively, include agriculture, consumer goods, finance, mining, property and construction, and trade and services. Moderation analysis shows a negative relationship between attention grabbing and abnormal returns, which weakens during black swan events. This suggests that the negative impact of attention grabbing on abnormal returns diminishes under extreme market conditions. The study highlights the behavioral dynamics of capital markets during rare and unpredictable events, emphasizing the relevance of behavioral finance. It also supports the notion of increasing integration among global financial markets, as evidenced by similar reactions in international capital markets. This research is limited to representative biases, specifically familiarity and attention grabbing. Other psychological biases beyond representativeness remain unexplored and warrant further study, particularly during crisis periods. Additionally, the use of secondary data suggests future research could benefit from primary data collection for deeper behavioral insights.